Knowledge about Tuberculosis in outpatients who visited College of Medical Sciences Teaching Hospital, Bharatpur, Nepal - Manandhar, N; Krishna, G (Journal of Institute of Medicine Nepal, 2013)
Background: Now a days Tuberculosis is a major public health problem in the world. Number of deaths due to tuberculosis is highest among the infectious diseases. Methods: The cross sectional study was carried out from May 2008 to July 2008 in the different out patient departments of College of Medical Sciences Teaching Hospital. A total of 500 patients belong to age > 15 years who visited various departments of College of Medical Sciences Teaching Hospital were randomly selected for the present study. Interview technique was used to collect information on a pre-designed and pre-tested questionnaire. Results: Out of total patient’s interview, 59% and 41% were male and female respectively. Majority of the outpatients had heard about the Tuberculosis disease. 73.3% of the respondents opinioned that T.B. can be acquired by infection. Conclusion: The study population has satisfactory knowledge about the etiology and transmission of the disease. There was poor knowledge about proper disposal of sputum which is an important aspect in regard to transmission of disease. There is need of imparting knowledge to the people about proper disposal of sputum to reduce the spread of disease and mortality due to T.B DOI: http://dx.doi.org/10.3126/joim.v34i1.9120 Journal of Institute of Medicine, April, 2012; 34:1 33-36